Securing data services: a security architecture design for private storage cloud based on HDFS. (1st January 2013) - Shen, Qingni; Yang, Yahui; Wu, Zhonghai; Wang, Dandan; Long, Min
With the growth of business, an enterprise would like to make its PSC (private storage cloud) approach an infrastructure service in a partner/public cloud. In such PSCs, there are some new data security issues, First, how to keep the data rest in the PSC isolated from internal and external attackers; second, how to make secure intra-cloud data migration within the enterprise; third, how to secure inter-cloud data migrating between the PSC and the partner/public cloud. In this paper, we propose an architecture design for enforcing data security services on the layer of HDFS in the PSC, including secure data isolation service, secure intra-cloud data migration service, and secure inter-cloud data migration service. Finally, it gives the prototype implemented as pluggable security modules in accord with our custom security policies through AOP (Aspect-Oriented Programming) method. The time cost is given and evaluated efficiently.